ANÁLISE DAS OCUPAÇÕES EM FAIXAS DE DOMÍNIO NO MODAL RODOVIÁRIO: REVISÃO DAS NORMAS E POTENCIAL APLICAÇÃO DO SENSORIAMENTO REMOTO NO APRIMORAMENTO DA GESTÃO DE TRÁFEGO (REMUNOM, 2025)
Road transport is the most widely used form of transport in Brazil, with high density and flows compared to other modes. It is responsible for 65% of cargo transported and almost 95% of passengers (CNT, 2024). This scenario leads to a significant increase in irregular occupations in road right-of-way, causing social and environmental impacts that compromise road safety. This study reviews current standards and regulations that determine guidelines for the design, construction, and monitoring of these roads, aiming at compliance with safety and sustainability standards. The analysis also explores the application of remote sensing as an effective tool for traffic monitoring and management, contributing to the preservation of lanes and adjacent lots.Keywords: Right-of-way, remote sensing, road management, occupation, road mode.